2022
DOI: 10.3390/bios12080570
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of MicroRNA-155 in Human Cells by Heterogeneous Enzyme-Linked Oligonucleotide Assay Coupled with Mismatched Catalytic Hairpin Assembly Reaction

Abstract: In the present work, we describe the development of a chemiluminescent enzyme-linked oligonucleotide assay coupled with mismatched catalytic hairpin assembly (mCHA) amplification for the quantitative determination of microRNA-155. To improve its sensitivity, a polymerase-free mCHA reaction was applied as an isothermal amplification method. The detection limit of the proposed assay was 400 fM. In addition, the high specificity of the assay was demonstrated. The proposed assay allowed assessment of the content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Oleg L. Bodulev et al combined a chemiluminescent enzyme-linked oligonucleotide assay with mismatched catalytic hairpin assembly amplification [ 5 ]. The case study of this approach for microRNA-155 assay demonstrated a low detection limit of 400 fM.…”
mentioning
confidence: 99%
“…Oleg L. Bodulev et al combined a chemiluminescent enzyme-linked oligonucleotide assay with mismatched catalytic hairpin assembly amplification [ 5 ]. The case study of this approach for microRNA-155 assay demonstrated a low detection limit of 400 fM.…”
mentioning
confidence: 99%